Studi Deteksi Utilitas Bawah Tanah dalam Rangka Pembangunan Jaringan Perpipaan SPAM Semarang Barat - Thesisa, Cilda (Media Komunikasi Dunia Ilmu Sipil (MoDuluS), 2025)
Underground utility detection is a crucial step in the pipeline construction project of the Semarang Barat Drinking Water Supply System (SPAM) to prevent potential conflicts with existing infrastructure. This study aims to identify and map underground utilities using Ground Penetrating Radar (GPR) and Pipe & Cable Locator methods. The results revealed four primary types of underground utilities: gas pipes (PGN), clean water pipes (PDAM), power cables, and fiber optic cables, located at varying depths ranging from 0.3 to 5 meters. Some utilities, particularly power cables, could not be fully mapped, although depth estimates were successfully obtained. The measurements also indicated depth deviations, with ±30 cm for GPR and approximately ±5% for the Pipe & Cable Locator. These findings highlight the importance of validating utility detection results prior to construction to minimize the risk of damaging existing infrastructure..